Conflicts in and around Space: Reflections on Mosque Conflicts' - Lundsteen, Martin (Journal of Muslims in Europe, 2020)
The 21st century has seen increasing attacks directed at Muslim places of worship, a social problem that has resulted in a whole array of investigations. This article suggests that the majority of this research on mosque conflicts fails to address the entrenched class dynamics and shifting geography of capitalist accumulation. Consequently, it complements this research by analysing the first mediatised conflict of its kind in Spain, the protest against the construction of a purpose-built mosque in Catalonia, Premià de Mar. The case demonstrates that the opposition was in fact a racist attack against Muslims answering to the economic interests of the local bourgeoisie. The ones acting it out, a section of the local working class, was convinced that this symbol of migrant presence would be a degrading feature that would jeopardise their recent social upward mobility. Hence it is fundamentally an expression of how racist logic is embedded in the spatial logic of capitalism in the 21st century.